Cleaning of a model food soil from horizontal plates by a moving vertical water jet. (17th February 2015) - Wilson, D.I.; Köhler, H.; Cai, L.; Majschak, J.-P.; Davidson, J.F.
Abstract: The removal of layers of a model food soil (dried Xanthan gum containing fluorescent ZnS particles) by a vertical water jet impinging normally on to the plate, generated by a solid stream nozzle which moves across the plate was reported byKöhler et al. (2014) . Their experiments investigated nozzle pressures from 0.5 to 2.0 barg; nozzle diameters from 0.84–2.66 mm, nozzle-layer separation of 20 mm, and nozzle traverse speeds of 2.1–126 mm s −1 . The flow parameters and separation are smaller than those typical of industrial jet cleaning operations. The model developed byWilson et al. (2014) [Chem. Eng. Sci. 109, 183–196] for cleaning of similar layers by a stationary impinging jet was modified to describe the case of moving nozzle. This new model predicted the trends observed in the experiments, and analysis of the data yielded a similar cleaning rate constant to that obtained previously for cleaning of similar layers by stationary jets. The model predicted a non-circular cleaning front which matched that extracted from new experiments in which the flow was interrupted in order to capture this feature. The model allowed the cleaning performance indicators suggested byKöhler et al. (2014) to be expressed quantitatively: these indicated that higher nozzle traverse speeds give increased cleaning time, energy and liquid consumption performance. Graphical abstract: Highlights: Removal of model food layers by a moving water jet is studied experimentally. The new analytical model predicts the observed cleaning front shape. The effect of process parameters on the cleaned region width is captured well. The cleaning rate constant obtained agrees with values from stationary jet tests.